(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
Independent work in physics fosters creative thinking and analytical abilities. This article describes the experience of organizing physics students’ independent work through the use of a lesson plan outline within the context of human capital formation. The effectiveness of this method in preparing highly qualified specialists with an advanced level of physics knowledge is demonstrated.